Comparison of the elements of cohesion in two Tadhkiras from Attar’s Tadhkirat al-Auliya Based on the systemic-functional Grammar of Halliday and Hasan - Samane Refahi (مطالعات زبانی و بلاغی)
Tadhkirat al-Auliya is the only prose of Attar. This book consists of a main and a supplementary part. There are different opinions about the author of the supplement. Some say its author is Attar, and others believe that someone else wrote and added it to Tadhkirat al-Auliya. This study has analyzed and compared the cohesion of the main section of Tadhkirat al-Auliya with the supplementary section in two sample Tadhkiras; Hallaj Tadhkira from the main section and Khavvas Tadhkira from the supplementary section. The study is carried out based on systemic-functional Grammar of Halliday and Hasan, according to which each text is examined from the perspective of three metafunctions: ideational metafunction, interpersonal metafunction and textual metafunction. In the study of textual metafunction, the method of discourse in the context of the work is discussed. Cohesion is one of the factors that is explored in the analysis of textual metafunction along with other factors. In the study of these two Tadhkiras, it was found that, although the Khavvas Tadhkira is shorter than the Hallaj Tadhkira, the number of cohesive elements in it, except in one case, is higher than the Hallaj Tadhkira and it shows more structural cohesion. It should be noted that these differences are not very remarkable, and when these elements are put together, the results are thought-provoking. The closeness of the number of elements of cohesion reveals the stylistic similarity of Tadhkiras to the reader. Assuming that the author of both Tadhkiras is Attar, this slight difference can be due to the passage of time and the use of new sources, which has led to more cohesion in supplementary Tadhkira.